Impacts of salinity stress on crop plants: improving salt tolerance through genetic and molecular dissection - Atta, Kousik; Mondal, Saptarshi; Gorai, Shouvik; Singh, Aditya Pratap; Kumari, Amrita; Ghosh, Tuhina; Roy, Arkaprava; Hembram, Suryakant; Gaikwad, Dinkar Jagannath; Mondal, Subhasis; Bhattacharya, Sudip; Jha, Uday Chand; et al. (Frontiers in Plant Science, 2023)
Indiscriminate use of recycled water in irrigation that contains a significant amount of salt ions, faulty agronomic practices such as improper fertilization etc. are gradually increasing soil salinity of arable lands across the globe. It is one of the major abiotic factors that inhibits overall plant growth through ionic imbalance, osmotic stress, oxidative stress, and reduced nutrient uptake. Plants have evolved with several adaptation strategies at morphological and molecular levels to withstand salinity stress. Among various approaches, harnessing the crop genetic variability across different genepools and developing salinity tolerant crop plants offer the most sustainable way of salt stress mitigation. Some important major gene(s)/genetic determinants controlling salinity tolerance have been uncovered using classical genetic approaches. However, due to its complex inheritance pattern makes breeding for salinity tolerance challenging. Subsequently, advances in bi-parental QTL mapping, genome wide association mapping, sequence based breeding approaches, and functional genomics have greatly assisted us underpinning the novel genetic variants controlling salinity stress tolerance across the whole genome in plant. This current review aims to shed light on physiological, biochemical, and molecular responses under salt stress, defence mechanisms of plants, underlying genetics of salt tolerance through bi-parental QTL mapping and Genome Wide Association Studies, and implication of Genomic Selection to breed salt tolerant lines.